The effects of color therapy on depression, stress, anxiety, and quality of life in hemodialysis patients: A randomized controlled trial - Bahcecioglu, Gulcan; Ozer, Zulfunaz; Karaca, Safiye Yanmis; Mollooglu, Mukadder; Ersoz, Kubra (Elsevier Science Inc, 2026)
Introduction: This study was conducted to examine the effects of color therapy on depression, anxiety, stress levels, and quality of life in individuals receiving hemodialysis treatment. Methods: This study was designed as a two-arm, parallel-group randomized controlled trial with baseline and post-intervention assessments. The study sample consisted of a total of 60 patients receiving hemodialysis treatment at a university hospital dialysis unit. The intervention group received color therapy for eight weeks, while the control group received no intervention. Data were collected before and after the color therapy intervention using Personal Information Form, Depression Anxiety Stress Scale-21, and the Quality of Life Index Dialysis Version III. Results: At the end of the 8-week study period, the color therapy group showed greater improvements than the control group in depression, anxiety, and stress scores. The between-group differences favored color therapy for depression [MD = -6.27, 95% CI -7.29 to -5.25, Cohen's d = 3.175], anxiety [MD = -6.50, 95% CI -7.68 to -5.32, Cohen's d = 2.843], and stress [MD = -7.70, 95% CI -8.73 to -6.67, Cohen's d = 3.870]. Quality of life also improved more in the color therapy group than in the control group [MD = 7.60, 95% CI 6.15 to 9.05, Cohen's d = 2.697]. No intervention-related adverse events were reported. Conclusion: Color therapy is an effective, safe, and feasible complementary nursing intervention that reduces depression, anxiety, and stress levels and improves quality of life in hemodialysis patients. These findings indicate that color therapy can be used as part of holistic nursing care in hemodialysis units and integrated into the nursing process. Clinical Trial Registration: NCT06879808
Keywords: Anxiety; Color Therapy; Depression; Hemodialysis; Nursing; Quality Of Life; Randomized Controlled Trial; Stress